Computational modeling of the deformation of the "bone–implant–prosthesis" system - Barbin, Kostiatyn (National Technical University "Kharkiv Polytechnic Institute", 2025)
The study investigates the deformation behavior of a "bone–implant–prosthesis" system using finite element analysis. It shows that increased friction at the bone–implant interface, due to osseointegration, improves system strength under static loading.
Keywords: finite element method; bone–implant–prosthesis system; osseointegration; friction coefficient; biomechanical modeling; stress analysis; prosthetic design